2014
DOI: 10.4067/s0717-92002014000200007
|View full text |Cite
|
Sign up to set email alerts
|

Efectos de la invasión del ligustro, Ligustrum lucidum, en la dinámica hídrica de las Yungas del noroeste Argentino

Abstract: SUMMARYArgentinean Yungas (subtropical montane forests) have high biodiversity and play a key role in regional watershed regulation. Ligustrum lucidum (glossy privet), native of China, is one of the dominant exotic tree species in secondary forests of this ecoregion. Due to its high growth rates and green foliage throughout the year -in contrast to native forests which are partially deciduous-the hypothesis is that water availability is reduced in glossy privet forests, especially during dry season (winter-spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 17 publications
0
12
0
5
Order By: Relevance
“…Studies assessing the variation among the year of the normalized difference vegetation index (NDVI), used as a proxy of transpiration (Zhang et al 2001), show higher values in L. lucidum – invaded forests than in native forests, particularly during the dry season, in subtropical montane forests of NW Argentina and dry forests of Central and northern Argentina (Hoyos 2007 ; Zamora Nazca et al 2014 ; Whitworth Hulse 2018 ). Zamora Nazca et al ( 2014 ) and Whitworth Hulse ( 2018 ) found that L. lucidum-invaded forests present 15% less annual average water content than adjacent native forests, and these differences increased to values of 30%, during the dry season. Deep soil water availability of small catchments is also lower in L. lucidum-invaded forest than in native forests dominated by Lithraea molleoides in dry forests of Central Argentina (Whitworth Hulse 2018 ), suggesting a reduction of groundwater recharge.…”
Section: Ecological Effects Of L Lucidum Invasionmentioning
confidence: 99%
“…Studies assessing the variation among the year of the normalized difference vegetation index (NDVI), used as a proxy of transpiration (Zhang et al 2001), show higher values in L. lucidum – invaded forests than in native forests, particularly during the dry season, in subtropical montane forests of NW Argentina and dry forests of Central and northern Argentina (Hoyos 2007 ; Zamora Nazca et al 2014 ; Whitworth Hulse 2018 ). Zamora Nazca et al ( 2014 ) and Whitworth Hulse ( 2018 ) found that L. lucidum-invaded forests present 15% less annual average water content than adjacent native forests, and these differences increased to values of 30%, during the dry season. Deep soil water availability of small catchments is also lower in L. lucidum-invaded forest than in native forests dominated by Lithraea molleoides in dry forests of Central Argentina (Whitworth Hulse 2018 ), suggesting a reduction of groundwater recharge.…”
Section: Ecological Effects Of L Lucidum Invasionmentioning
confidence: 99%
“…Finally, once the species is well established, privet may form mono-specific stands that will dominate the entire tree community of the invaded habitat. The effects of privet on native forest are evident, modifying community species composition (Ayup et al 2014) and ecosystem functions (such as nutrient turnover), and producing shifts in environmental conditions such as soil moisture and light availability (Zamora Nasca et al 2014). Additionally, privet can slowly invade the native forests without human intervention (Malizia et al 2017), because the species is dispersed not only by humans but also by native fruit-eating birds (Aragón and Groom 2003).…”
Section: Wp3 Explore Long-term Management Success Criteriamentioning
confidence: 99%
“…For example, Zamora Nasca et al. () suggested that secondary forests dominated by L. lucidum (i.e. monospecific stands) consumed more water compared to native secondary forests, especially during the dry season (winter–spring); indeed soil water content in secondary forests dominated by L. lucidum was ca.…”
Section: Discussionmentioning
confidence: 99%
“…productivity and water dynamics; Zamora Nasca et al. ). This idea is consistent with the results of Hoyos et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation